Identification and Characterization of Separase Inhibitors (Sepins) for Cancer Therapy. (July 2014) - Zhang, Nenggang; Scorsone, Kathleen; Ge, Gouqing; Kaffes, Caterina C.; Dobrolecki, Lacey E.; Mukherjee, Malini; Lewis, Michael T.; Berg, Stacey; Stephan, Clifford C.; Pati, Debananda
Separase is an endopeptidase that cleaves cohesin subunit Rad21, facilitating the repair of DNA damage during interphase and the resolution of sister chromatid cohesion at anaphase. Separase activity is negatively regulated by securin and Cdk1–cyclin B in vivo. Separase overexpression is reported in a broad range of human tumors, and its overexpression in mouse models results in tumorigenesis. To elucidate further the mechanism of separase function and to test if inhibition of overexpressed separase can be used as a strategy to inhibit tumor-cell proliferation, small-molecule inhibitors of separase enzyme are essential. Here, we report a high-throughput screening for separase inhibitors (Sepins). We developed a fluorogenic separase assay using rhodamine 110–conjugated Rad21 peptide as substrate and screened a small-molecule compound library. We identified a noncompetitive inhibitor of separase called Sepin-1 that inhibits separase enzymatic activity with a half maximal inhibitory concentration (IC50 ) of 14.8 µM. Sepin-1 can inhibit the growth of human cancer cell lines and breast cancer xenograft tumors in mice by inhibiting cell proliferation and inducing apoptosis. The sensitivity to Sepin-1 in most cases is positively correlated to the level of separase in both cancer cell lines and tumors.